PENANGANAN TINDAK PIDANA PERDAGANGAN ORANG DALAM PERSPEKTIF GLOBAL DAN ISLAM DI PROVINSI SUMATERA SELATAN - Rr Rina Antasari (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This article discusses how criminal act of human trafficking is handled related to global perspective and Islamic perspective. This is a case in South Sumatera. There are some forms of human trafficking and this crime should come to serious responses because it deals with human right. This research applies a conceptual approach, statute approach, philosophical approach, and sociology approach to law. The human trafficking, in this case, exploited the victims into underpaid workers, baggers, immigrant workers, housemaid and many more. This practice keeps in progress because of the low education level of the victims, strong economic reason, domestic violence, and other violence. The government of South Sumatera responses to this by establishing a special team against human trafficking which involves government institutions, NGOs and mass media. The legal act from the government of South Sumatera has been doing but it still has the burden for law enforcement